2002
DOI: 10.1152/ajpregu.2002.282.2.r431
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and insulin regulation of fetal ovine white adipose tissue leptin expression

Abstract: Leptin, an adipocyte-derived factor, has multiple biological roles including mitogenesis. We investigated the effect of normal development, acute and chronic hyperglycemia and hypoglycemia, and selective acute hyperglycemia, or hyperinsulinemia, on fetal ovine white adipose tissue (WAT) leptin mRNA concentrations. Leptin mRNA amounts expressed as a ratio to the internal control ribosomal S2 mRNA decreased threefold with advancing gestational age (P < 0.05). This gestational decrease was opposite to the 10-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…Our current Dex-associated changes are consistent with that reported previously in the intrauterine growth-restricted (IUGR) progeny (8,39). In the IUGR progeny, calorie restriction begins in utero, resulting in persistence of growth failure into adulthood (27,49).…”
Section: Day Oldsupporting
confidence: 90%
See 1 more Smart Citation
“…Our current Dex-associated changes are consistent with that reported previously in the intrauterine growth-restricted (IUGR) progeny (8,39). In the IUGR progeny, calorie restriction begins in utero, resulting in persistence of growth failure into adulthood (27,49).…”
Section: Day Oldsupporting
confidence: 90%
“…In the IUGR progeny, calorie restriction begins in utero, resulting in persistence of growth failure into adulthood (27,49). The IUGR offspring has low insulin (39) and leptin concentrations in utero (8), while the impact on endogenous corticosterone concentrations has been controversial, with some studies demonstrating no effect (4, 36) and others showing an increase that may cause the programming effects observed in the adult (30,33). In conjunction with these hormonal effects, a sustained postnatal increase in hypothalamic neuropeptide Y concentrations is observed in the IUGR (39) and in the maternally deprived offspring (24).…”
Section: Day Oldmentioning
confidence: 99%
“…In fetal sheep, plasma leptin concentrations increased transiently 24-48 h after the onset of fetal cortisol infusion but were normal on the fifth day of infusion at the time when perirenal adipose tissue was collected in the present study (Forhead et al 2002). In previous studies of fetal sheep, both increases and decreases in leptin expression have been observed in perirenal adipose tissue over the same period of late gestation examined in the present study (Yuen et al 1999, Devasker et al 2002. This may be explained, in part, by breed differences in leptin expression (Dandrea 2001) but may also reflect differences in nutritional intake by the ewes between early to mid gestation, when a reduction in maternal food intake results in increased leptin mRNA in fetal adipose tissue as measured near to term .…”
Section: Discussionsupporting
confidence: 53%
“…This is an example of a sexspecific "neuropeptide imprinting" effect secondary to postnatal leptin exposure constituting "hormonal imprinting." The significance of our observations relates to the offspring of a diabetic mother exhibiting high levels of circulating leptin at birth (17,32) and low concentrations of brain NPY just before birth (49). The level of hyperleptinemia at birth may result in either leptin sensitivity or resistance, thereby contributing toward heterogeneity in clinical presentation by predetermining the adult phenotype.…”
Section: Discussionmentioning
confidence: 87%